Efektivitas Model Pembelajaran Kooperatif Tipe Team Game Tournament Terhadap Hasil Belajar Siswa Kelas XI TITL pada Mata Pelajaran Instalasi Tenaga Listrik - Wahyu Tri Prastyo; Dwiprima Elvanny Myori (PAKAR Pendidikan, 2023)
The absence of creative and innovative learning methods in Vocational High Schools has led to this research being conducted. This study aims to determine how effective the TGT (Team Game Tournament) learning model is on student learning outcomes in the subject of electric power installation. The subjects of this study were students of class XI TITL 1 at SMK Negeri 5 Padang in the 2022/2023 academic year, with a total of 30 students. The research design used was a quasy experimental design with one group pretest-posttest. In this study the instruments used included tests and questionnaires. Pre-test, post-test, and questionnaires were used in this study to collect data. Effect size analysis, homogeneity test, and normality test were used for data analysis. Based on the research findings, it is evident that class XI TITL 1 students at SMKN 5 Padang use the TGT learning model very successfully. The average pretest score was 63.87, the posttest average score was 79.87, and the calculation of Cohen's effect size analysis was 1.73 (95.5%), indicating a large category since TGT learning was used. The TGT learning model has a significant impact on improving student learning outcomes because it can increase students' creativity and enthusiasm in learning. Based on the results of the questionnaire, 56% of respondents strongly agreed that the TGT learning model was very effective. It can be concluded that students consider the TGT learning model as an interesting and efficient learning method that can increase their enthusiasm for learning in the electric power installation subject.